KESADARAN MAHASISWA AKUNTANSI STIENU JEPARA MENGENAI ETIKA DALAM AUDIT INTERNAL - Marisan, Ichwan; Nahar, Aida; Sofwan, Ali (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2014)
The ability of internal auditors in the future, namely current students, to recognize and reactappropriately to the ethical dilemma is a problem that gets the attention of the accountingprofession. Based on this thinking it needs a study to measure the ethical awareness of thestudents when they are presented with the dilemma of internal audit situation, where they have tomake decisions based on ethical considerations. The aim of this study was to examine differencesin the accounting student awareness of ethical decision-making between men and women auditand examine differences in ethical awareness in decision making audit between students whohave taken courses with the auditing yet. Ethical decision-making variables broken down intosix scenarios. Scenario odd number (1, 3, 5) is an ethical action while the scenario is even (2, 4,Â 6) is an unethical act. The study population was a sample of accounting students with studentsÂ who are auditing the class I / II. Methods of data collection by questionnaires distributed directlyto students while in class. The analytical method used is a different test for non-parametric datadistribution is not normal. The conclusion is the first, students have the awareness of the ethicaldecision-making, but for ethical decision-making is not only one of the three scenarios scenariowas realized. Second, in general women are more able to take unethical decisions than men.Women are able to feel such an action is unethical than men. As for ethical decision-making nodistinction between men and women. Third, there was no difference in ethical decision makingas well as unethical among students who have attended the courses who have not followed theauditing auditing.